Terahertz and soft x rays radiation from suddenly created plasma layer - Gildenburg, V.B.; Vvedenskii, N.V. (Вопросы атомной науки и техники, 2005)
We study in this paper the effect of shock excitation of leaky and surface modes by the p-polarized electromagnetic wave incident on the rapidly ionized gaseous or solid layer. The amplitudes of these modes are calculated through the use of Laplace transforms. The results obtained show the potentialities for applying of the phenomenon of leaky modes excitation for generation (at corresponding density of ionized medium) of terahertz and soft x rays radiation. У даній роботі досліджується ефект ударного збурення поверхневих і хвиль, що витікають, p-поляризованою електромагнітною хвилею, що падає на швидко іонізуємий газоподібний або твердотільний шар. За допомогою перетворення Лапласа розраховані амплітуди цих хвиль. Отримані результати вказують на можливість використання ефекту збудження хвиль, що витікають, для генерації (при відповідній густині середовища, що іонізується) терагерцового і м'якого рентгенівського випромінювання В настоящей работе исследуется эффект ударного возбуждения поверхностных и вытекающих волн p-поляризованной электромагнитной волной, падающей на быстро ионизируемый газообразный или твердотельный слой. С помощью преобразования Лапласа рассчитаны амплитуды этих волн. Полученные результаты указывают на возможность использования эффекта возбуждения вытекающих волн для генерации (при соответствующих плотностях ионизируемой среды) терагерцового и мягкого рентгеновского излучения.